Principal's Leadership on “Sekolah Penggerak” Effectiveness in Improving the Quality of Education - Nafisah, Aisyah Durrotun; Antika, Dewi Hajar Windi; Latiana, Lita; Formen, Ali; Maronta, Yusuf (Attractive : Innovative Education Journal, 2022)
The purpose of this study was to determine the effectiveness of "moving schools" in improving the quality of education. This research is a descriptive qualitative type with interview, observation, and documentation data collection techniques. Researchers conducted participant observations of principals and teachers at Janeta Weleri Kindergarten and Muslimat NU 06 Lanji Kindergarten with research subjects there were 2 principals and 4 teachers. The results showed that the Principal of TK Janeta Weleri and TK Muslimat NU 06 Lanji as Leaders in schools were able to become the locomotive of change in schools. Learning is planned according to students' abilities and various activities are expected can make students comfortable and happy when learning at school.